2015
DOI: 10.5901/mjss.2015.v6n5s2p590
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hazards and Health Status of Trash Picker Children in Faisalabad City, Punjab, Pakistan

Abstract: Trash picking is an inferior, exploitative and inhumane economic activity; considered as the most vulnerable and neglected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…Migrant undocumented workers may not feel welcome at health facilities [ 5 , 6 ]. Additionally, informal economy workers may have less access to occupational health education and services; resulting in less knowledge of hazards and their control, poor access to personal protective equipment, and low health services coverage [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Migrant undocumented workers may not feel welcome at health facilities [ 5 , 6 ]. Additionally, informal economy workers may have less access to occupational health education and services; resulting in less knowledge of hazards and their control, poor access to personal protective equipment, and low health services coverage [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The practice clearly shows the scavengers' lack of knowledge of the risk a dirty piece of cloth can pose to their wound. In addition, the absence of personal protective gear was largely noted among scavengers in Pakistan (Batool et al, 2015;Majeed et al, 2016). As part of the unhygienic practices, it was also observed that the sanitary condition of the participants' houses was poor.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] A study by Batool et al . [ 15 ] in Pakistan showed that 79% of ragpickers faced hurdles of sharps and broken glasses during ragpicking.…”
Section: Discussionmentioning
confidence: 99%
“…Many waste pickers complain about flies and mosquitoes act as a nuisance while working. [ 15 ] More than half of study population (baseline) had awareness regarding vector-borne diseases arising from these waste. Solid waste is associated with several specific vector-borne diseases.…”
Section: Discussionmentioning
confidence: 99%